Effect of supplementary concentrate feeding to lambs on the growth performance and body morphometry - MOHANTY, J D; PANIGRAHI, B; PANDA, N; BAGH, J; SAMAL, L (The Indian Journal of Animal Sciences, 2023)
A study was conducted to evaluate the effect of feeding concentrate to suckling lambs on their performance. Experiment comprised 40 day old suckling lambs having 1.56 kg average birth weight, with 20 female and 20 male lambs selected randomly from the flocks of four farmers in village Mundida, Odisha. The male and female lambs were divided into two experimental groups so that each experimental group of 20 lambs consisted of 10 male and equal numbers of females. Group 1 (Control) was maintained on suckling and grazing only, while Group 2, balanced concentrate mixture was supplemented in addition to suckling and grazing. Concentrate was supplemented from 2nd fortnight upto 6th fortnight of age. Body weight, average daily gain were recorded upto14th fortnight of age. Body measurements were recorded at every fortnight interval. Either of the male or female lambs group body weight did not differ significantly till the 2nd fortnight, while upon concentrate supplementation from 2nd fortnight, the lambs in Group 2 showed significantly higher body weights and average daily gain from 3rd fortnight till the end of observation at every stage (14th fortnight). Body measurements differences between the groups were observed only after commencement of the concentrate supplementation which resulted in higher values for the lambs in Group 2 from 4th or 5th till the last fortnight. Results revealed that supplementation of concentrate to the four weeks old grazing lambs for a period of 8 weeks improved the body weight, weight gain and reduces cost of lamb production.